Epidemiology and Prevention of Tuberculosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The incidence of tuberculosis determines the level of socio-economic tension in society, regardless of the social composition of population groups. Negative environmental changes and socio-economic problems affect the usual way of life of the majority of the population, provoking changes in the immune status of almost all members of society. It is impossible to carry out measures to prevent tuberculosis without in-depth knowledge of the various factors that determine the development of this disease for each individual case in a social group. Anti-tuberculosis measures are also ineffective without assessing the medical and social characteristics of the formation of morbidity among certain groups.